Implementasi Model Pembelajaran Kooperatif Tipe Two Stay-Two Stray-Media Video pada SDN 8 Langkai Palangka Raya - Rita Rahmaniati; Supardi Supardi; Abdul Malik (Jurnal Hadratul Madaniyah, 2018)
This research aims to: (1) To know the activity of students of class IV SDN-8 Langkai by applying TSTS learning model and video media on science learning, (2) To know the improvement of science learning result after applying TSTS learning model and video media on science learning. Subjects in this study were all students of class IV SDN-8 Langkai Palangkaraya, Central Kalimantan, amounting to 35 people where there are 15 male students and 20 female students. The research method used by researcher is using classroom action research method (PTK) with two cycles. Analytical techniques in this study using qualitative and quantitative data analysis. The result of the research shows that: (1) Activity of the students is very active after applying TSTS and video media model in science learning subject, (2) Improving learners' learning outcomes by applying TSTS learning model and video media in science grade IV SDN- 8 Langkai Palangkaraya is increasing. This is evidenced from the achievement of learning outcomes of learners on the results of observations obtained an average value of 63.61 and 44.44% of completeness in the classical, included in the criteria has not been achieved. Then in the first cycle increased with an average value of 66.28 and 50.42% classical completeness, also still included in the criteria has not been achieved. Then on the second cycle increased with an average value of 77.85 and 88.57% classical completeness or 31 students who complete learning IPA in the material kinds of styles.